Gender and grade level as predictors of attributions in reading and mathematics in students of Compulsory Secondary Education - Inglés, Cándido J.; Díaz Herrero, Ángela; GarcíaFernández, José M.; Ruiz Esteban, Cecilia (Anales de Psicología / Annals of Psychology, 2011)
This study analyzed the predictive role of the gender and grade level on academic self-attributions in language and mathematics. The Sydney Attribution Scale (SAS) was administered to 2,022 students from grades 7 to 10. Logistic regression analyses indicated that gender and grade were statistically significant predictors of academic self-attributions, al-though the results varied for each of the scales of the SAS. The results showed that the causal attributions were different in boys and girls de-pending on the academic content area. The boys showed a more positive attributional style in mathematics while girls showed more positive aca-demic self-attributions in reading. It was also noted that in the higher grades, both boys and girls, further attributed their failures in reading and math to internal causes.